Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/lary.27121
|View full text |Cite
|
Sign up to set email alerts
|

Office‐based esophageal dilation in head and neck cancer: Safety, feasibility, and cost analysis

Abstract: 4. Laryngoscope, 128:2261-2267, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…From this selection, another 49 articles were excluded because inclusion criteria were not met. The search update yielded three additional articles suitable for inclusion [20-22]. In total, 13 articles were included [9-11, 20-29].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…From this selection, another 49 articles were excluded because inclusion criteria were not met. The search update yielded three additional articles suitable for inclusion [20-22]. In total, 13 articles were included [9-11, 20-29].…”
Section: Resultsmentioning
confidence: 99%
“…All articles used financial data based on actual cases, except for the studies of Castillo Farías et al [25] and Schutte et al [21], who estimated costs based on costs of materials, facilities and personnel required to perform these procedures in general. Hospital costs were discussed in seven studies [9, 10, 21, 22, 25-27]; hospital charges in eight studies [9, 11, 20, 23, 24, 27-29]. All included studies reported on costs from a hospital’s perspective.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations